Participatory breeding in the Peruvian highlands: Opportunities and challenges for promoting conservation and sustainable use of underutilized crops. Issue 5 (13th May 2014) - Galluzzi, Gea; Estrada, Rigoberto; Apaza, Vidal; Gamarra, Mirihan; Pérez, Ángel; Gamarra, Gilberto; Altamirano, Ana; Cáceres, Gladys; Gonza, Víctor; Sevilla, Ricardo; Noriega, Isabel López; Jäger, Matthias
Abstract: Underutilized crops tend to harbor high levels of genetic diversity, be maintained on-farm in small-scale farming systems and be relatively neglected by formal research and development strategies, including breeding programs. While high genetic variability allows these crops to adapt to marginal environments, inappropriate management practices and reductions in population sizes in individual farmers' plots may lead to productivity loss and poor harvests. This situation further limits their cultivation and use, notwithstanding the potential these crops may hold for diversification of agricultural systems, food security and market development. Peru hosts a wealth of native agrobiodiversity, which includes many underutilized crops. To improve their performance and promote their continued conservation and use, a participatory breeding program was developed on five underutilized crops of the Peruvian highlands; the breeding approach, based on a combination of evolutionary and participatory methods, is designed to achieve a balance between yield improvement and maintenance of genetic diversity. Preliminary results in quinoa and amaranth are encouraging, fostering further engagement of farmers by increasing availability of quality seed for downstream uses. However, methodological, financial and institutional issues need to be addressed for the effort to be expanded and upscaled. This paper provides an overall description of the initiative as well as a discussion on early results obtained in quinoa and amaranth, highlighting those aspects that make this approach particularly relevant for minor crops and identifying the opportunities and challenges for the initiative to move forward.